2013
DOI: 10.1111/nph.12525
|View full text |Cite
|
Sign up to set email alerts
|

Pistillate flowers experience more pollen limitation and less geitonogamy than perfect flowers in a gynomonoecious herb

Abstract: SummaryGynomonoecy, a sexual system in which plants have both pistillate (female) flowers and perfect (hermaphroditic) flowers, occurs in at least 15 families, but the differential reproductive strategies of the two flower morphs within one individual remain unclear.Racemes of Eremurus anisopterus (Xanthorrhoeaceae) have basal pistillate and distal perfect flowers. To compare sex allocation and reproductive success between the two flower morphs, we measured floral traits, pollinator preferences, and pollen mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 33 publications
(56 reference statements)
2
27
0
Order By: Relevance
“…Our ancestral character state reconstruction showed that the reproductive mode monoecy shifted to gynomonoecy; this shift occurs in the nodes involved in the dispersal event with directions north to south. It has been postulated that gynomonoecy (plants have both female flowers and hermaphroditic flowers) benefits outcrossing, as hermaphroditic flowers promote more seeds, whereas female flowers counterbalance the loss of male function through better seed quality (Mamut et al ., ). It is possible that this shift in reproductive mode may have speeded up the establishment of seedlings after the dispersal processes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our ancestral character state reconstruction showed that the reproductive mode monoecy shifted to gynomonoecy; this shift occurs in the nodes involved in the dispersal event with directions north to south. It has been postulated that gynomonoecy (plants have both female flowers and hermaphroditic flowers) benefits outcrossing, as hermaphroditic flowers promote more seeds, whereas female flowers counterbalance the loss of male function through better seed quality (Mamut et al ., ). It is possible that this shift in reproductive mode may have speeded up the establishment of seedlings after the dispersal processes.…”
Section: Discussionmentioning
confidence: 97%
“…Based on phylogenetic and biogeographical analyses, we test whether the current disjunct distribution of Munroa is explained by any of the above‐mentioned hypotheses. In a spatio‐temporal framework, we examine whether shifts in attributes, such as ploidy (diploidy to polyploidy; Linder & Barker, ), habit (perennial to annual; Jakob et al ., ), reproductive system (monoecy to gynomonoecy; Mamut et al ., ) or a number of vegetative and floral characters that favour dispersal or establishment in new habitats, occurred at the nodes at which dispersal events happened.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, outside of the Asteraceae, gynomonoecy is found in only 3% of angiosperm genera (Torices et al., ). In some of these cases, gynomonoecy is functional, and rather than female flowers with no trace of stamens as in Asteraceae, these species present sterile anthers or staminodes in their female flowers (Bernardello et al., ; Méndez and Munzinger, ; Mamut et al., ). In other cases, gynomonoecy occurs as a manifestation of polymorphic sexual systems in dioecious species (Koelewijn and Van Damme, ; Onodera et al., ; Casimiro‐Soriguer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Hermaphroditism, coupled with production of multiple flowers per individual and the composite nature of individual flowers (perianth whorls, androecium, and gynoecium), allows considerable scope for plastic and evolutionary modification of the organization of female and male functions on individual plants (see Lloyd and Bawa 1984;Diggle et al 2011;Torices et al 2011;Diggle 2014). Importantly, this combination of characters enables division of labor among flowers, including pollinator attraction (bisexual and sterile flowers: Morales et al 2013) and the sex roles (e.g., Harder et al 2000;Vallejo-Marín and Rausher 2007a, b;Mamut et al 2014), and reduces sexual interference (Barrett 2002b).…”
mentioning
confidence: 99%